PENGARUH MEDIA PEMBELAJARAN INTERAKTIF BERBASIS POP UP BOOK TERHADAP KEMAMPUAN MEMBACA PERMULAAN BAHASA INDONESIA - Berkatul Jannah; Masrul; M. Syahrul Rizal; Musnar Indra Daulay; Yanti Yandri Kusuma (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This research is motivated by the low initial reading skills of students. One of the efforts offered to improve students' initial reading skills is to use Pop up book learning media facilities. This study aims to determine the effect of Pop up book- based learning media on the initial reading skills of students in class 1 Salafiyah Ula Ibnu Jarir. This type of research is a quasi-experimental study with a Nonequivalent Control Group Design. The data collection techniques for this study were in the form of observation, tests, and documentation. The experimental class was class 1 Banat and the control class was class 1 Banin Salafiyah Ula Ibnu Jarir. The data analysis technique to test the hypothesis used the t-test formula which was preceded by a normality test and homogeneity of variance. The results of this study indicate that the ability to read beginning using Pop up book media is higher than the ability to read beginning using the conventional model. With the results of the t-test at a significance level of 5%, the sig value (2-tailed) (0.00) <a (0.05) was obtained. This shows that the influence of interactive media based on pop-up books is more effective than conventional learning models. So it can be concluded that there is an influence of pop-up book-based learning media on the initial reading ability of grade 1 Salafiyah Ula Ibnu Jarir students.